The Pedagogical Intervention Regarding Advertising and Sports (Journal of Parents and Teachers, 2024)
Advertising is an aspect of our daily lives that focuses solely on profit, often without considering some of the consequences it may generate. Regarding sports, it is evident that advertising establishes relationships that can be very detrimental to young people, associating something that could be healthy and educational with tobacco, alcohol, or gambling. Despite this, certain advertisements advocate for proper education, such as the case of the ONCE (Spanish Organization for the Blind). There are regulations in place, but they are often overlooked to prevent such associations from happening.